Synthesis and Characterization of Chitosan-Citrate Microparticle Using Ionic Gelation Methods - Latupeirissa, Jolantje; Tanasale, Matheis F. J. D. P.; Fransina, Eirene Grace; Noya, Alesya (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
A study has been conducted which aims to synthesize chitosan-citrate using ionic gelation method and its characterization with FTIR, SEM, SAA and PSA, as well as solubility and swelling tests. The results showed that chitosan reacted with sodium citrate produces chitosan-citrate particles. The product of chitosan-citrate has a rough and thickened surface morphology. Surface area of chitosan-citrate obtained is 35.233 m2/g and pore size is 0.027 cc/g, smaller than chitosan. Based on solubility and swelling tests in acidic, alkaline, and neutral media, chitosan-citrate has good resistance and low swelling effect.